TRANSLATING GANTANG TUMBA CULTURAL TERMS IN KARONESE LANGUAGE INTO ENGLISH - Sembiring, Milisi; Girsang, Martina (Universitas Islam Sumatera Utara (UISU), 2022)
This article aims to translate and analyze the cultural terms in Gantang Tumba texts of Karonese language into English. The problem in translating the cultural terms in the source language into the target language is mostly related to culture, they are untranslatable. Conceptual research is applied to get the data while translation and critical discourse analysis are used to analyze the data. The researchers analyze all data and use Newmark’s (1988) translation procedures to translate cultural terms in the Gantang Tumba texts into English. The data are collected from participants of Gantang Tumba of wedding ceremonies in Tiga Binanga, Karo regency. The research results show that some of the cultural terms in the SL have no equivalences in the TL; they are untranslatable. Tukor, batang unjuken, rudang-rudang, perseninaan, gamber inget-inget, si ngalo bere- bere, si ngalo perbibin, si ngalo perkempun, si rembah ku lau, perkembaren, and ulu emas are cultural terms in the negotiation of gantang tumba text which have no equivalences in the TL.